Dukungan Psikososial Pada Lanjut Usia Dengan Sosialisasi Dan Latihan Senam Otak : - Lenny , Lenny; Saripah , Eli; Siregar, Hasbunsyah (Jurnal Pengabdian Mitra Persada, 2025)
The elderly population is increasing in number. This is a reality that cannot be avoided. The higher the elderly population, the more elderly people will need care. The world's population is aging rapidly. Between 2000-2050, the proportion of the world's population aged 60 years and over is expected to increase from 605 million to two billion in the same period. The projected proportion of the population aged 60 and over in 2015-2035 in Indonesia is 8.49% in 2015, 9.99% in 2020, 11.83% in 2025, 13.82% in 2030 and 15.77% in 2035. % (RI Ministry of Health, 2020). At the Mamboro Community Health Center, the elderly have never received information about mental health, nor have they participated in a psychosocial support program for the elderly to increase mental health resilience in the elderly. The Mamboro Health Center also does not have a program and has never held activities related to mental health for the elderly. Increasing knowledge about mental health can have an impact on the elderly themselves because good mental health is important to maintain the cognitive abilities of the elderly. The concept of mental health literacy refers to increasing knowledge and beliefs about mental disorders and their management or prevention.